Two-Dimensional Transition Metal Dichalcogenide: Synthesis, Characterization, and Application in Candlelight OLED - Dipanshu Sharma; Sanna Gull; Anbalagan Ramakrishnan; Sushanta Lenka; Anil Kumar; Krishan Kumar; Pin-Kuan Lin; Ching-Wu Wang; Sinn-Wen Chen; Saulius Grigalevicius; Jwo-Huei Jou (Molecules)
Low-color-temperature candlelight organic light-emitting diodes (OLEDs) offer a healthier lighting alternative by minimizing blue light exposure, which is known to disrupt circadian rhythms, suppress melatonin, and potentially harm the retina with prolonged use. In this study, we explore the integration of transition metal dichalcogenides (TMDs), specifically molybdenum disulfide (MoS2) and tungsten disulfide (WS2), into the hole injection layers (HILs) of OLEDs to enhance their performance. The TMDs, which are known for their superior carrier mobility, optical properties, and 2D layered structure, were doped at levels of 0%, 5%, 10%, and 15% in PEDOT:PSS-based HILs. Our findings reveal that OLEDs doped with 10% MoS2 exhibit notable enhancements in power efficacy (PE), current efficacy (CE), and external quantum efficiency (EQE) of approximately 39%, 21%, and 40%, respectively. In comparison, OLEDs incorporating 10% of WS2 achieve a PE of 28%, a CE of 20%, and an EQE of 35%. The enhanced performance of the MoS2-doped devices is attributed to their superior hole injection and balanced carrier transport properties, resulting in more efficient operation. These results highlight the potential of incorporating 2D TMDs, especially MoS2, into OLED technology as a promising strategy to enhance energy efficiency. This approach aligns with environmental, social, and governance (ESG) goals by emphasizing reduced environmental impact and promoting ethical practices in technology development. The improved performance metrics of these TMD-doped OLEDs suggest a viable path towards creating more energy-efficient and health-conscious lighting solutions.